DESIGN OF FISHING PREVENTION POLICY USING TRAWL IN THE BENGKULU COASTAL AREA - Aprilia Dewi Lestari; Bobby Mandala Putra; Rahinam Dani (Yayasan Wayan Marwan Pulungan, 2024)
This research aims to design a policy to prevent fishing using trawls in the Bengkulu coastal area. This research uses a qualitative approach using descriptive methods. This research uses Birkland's (2015) theory, which contains five elements, namely, the goals of the policy, the causal model, the tools of the policy, the targets of the policy, and the implementation of the policy. The informants in this research were 7 people consisting of 2 fishermen, 1 person from law enforcement, 2 people from the bureaucracy, 1 person from previous researchers, and 1 person from the organization. The research results are based on the aim of the policy to prevent the use of trawls, which is to preserve the sea and prevent conflicts between traditional fishermen and trawl fishermen. From the causal model, several causes and consequences will arise if the policy is implemented, including impacts on social, economic, and environmental impacts. From the dimension of policy tools, there are several alternative policies as tools that can be produced to prevent the use of trawling, namely in the form of 1. Confiscating fishing gear, 2. Creating a monitoring team from various institutional elements, 3. Providing sanctions and criminal penalties, 4. Providing zone boundaries. Where the use of trawls is prohibited, 5. Conduct patrols every week by changing officers continuously, 6. Conduct outreach about the dangers of using trawls and the importance of marine conservation,